Development and Preliminary Psychometric Evaluation of the Spiritual Needs Scale for Older Adults Receiving Palliative Care - Linan Cheng; Qian Chen (Healthcare, 2026)
Background: Meeting the spiritual needs of older adults receiving palliative care requires culturally sensitive and psychometrically sound assessment instruments. This study aimed to develop and evaluate the psychometric properties of the Spiritual Needs Scale (SNS) for older adults receiving palliative care. Methods: The primary version of the SNS was developed through a scoping review, in-depth interviews, Rodgers’ concept analysis, and expert consultation. A consecutive sample of 395 older adults receiving palliative care was recruited from the inpatient wards of two university-affiliated hospitals to evaluate the psychometric properties of the SNS. Validity assessment included content, face, and construct validity, while reliability was evaluated through Cronbach’s alpha and test–retest measures. Additionally, ceiling and floor effects were examined. Results: The SNS consists of 40 items. The scale demonstrated excellent content validity, with an S-CVI/Ave of 0.98 and an S-CVI/UA of 0.77. Exploratory factor analysis (EFA) revealed six factors that explain 65.595% of the total variance, which included connection with oneself and others, transcendence, connection with nature, reflection on life’s meaning, seeking life’s meaning, and a sense of belonging. The overall Cronbach’s alpha coefficient for the scale was 0.963, with coefficients for the six factors ranging from 0.852 to 0.920. The scale’s retest reliability was 0.853. Conclusions: The SNS demonstrated satisfactory validity and reliability for assessing the spiritual needs of older adults receiving palliative care. Further studies are needed to validate the scale in different cultural and clinical populations.